Cash transfers and female labor force participation: the case of AUH in Argentina - Garganta, Santiago (2017)
In this paper, we estimate the impact on female labor force participation of a massive conditional cash transfer program—Universal Child Allowance, AUH—launched in Argentina in 2009. We identify the intention-to-treat effect by comparing eligible and non-eligible women over time through a diff-in-diff methodology. The results suggest a negative and economically significant effect of the program on female labor force participation. The disincentive to participate is present for married women, while the effect is not statistically significant for unmarried women with children. We also find evidence on the heterogeneity of the effect depending on woman’s education, husband’s employment status, number and age of children, and whether the woman is the main responsible of domestic chores. The relatively large value of the benefit and the fact that transfers are mostly directed to mothers may explain the sizeable effect of the program on female labor supply. The welfare implications of the results are not clear and deserve further inspection.